Peran Good Governance dalam Memediasi Hubungan Foreign Direct Investment terhadap Pertumbuhan Ekonomi - Fadeli Yusuf Afif; Ukhti Ciptawaty (Jurusan Ilmu Ekonomi dan Studi Pembangunan Fakultas Ekonomi dan Bisnis Universitas Lambung, 2026)
This study aims to analyze the effect of Foreign Direct Investment (FDI) on economic growth by incorporating the mediating role of good governance. While FDI is widely regarded as a key driver of economic growth in developing countries, its effectiveness largely depends on the quality of institutions and governance frameworks. This study employs a quantitative approach using the Structural Equation Modeling–Partial Least Squares (SEM-PLS) method, based on Indonesia’s secondary data from 2002 to 2013, sourced from the World Development Indicators (WDI) and Worldwide Governance Indicators (WGI). Good governance is measured through six key dimensions: control of corruption, government effectiveness, political stability, rule of law, regulatory quality, and voice and accountability. The results indicate that FDI has a positive effect on good governance, and good governance significantly influences economic growth. In addition, FDI also exerts a direct effect on economic growth, although its magnitude is smaller than its indirect effect through governance. These findings suggest that good governance plays a crucial mediating role in strengthening the relationship between FDI and economic growth, while enhancing the effectiveness of foreign investment in improving productivity and economic capacity. This study contributes empirically by emphasizing the importance of institutional quality in maximizing the benefits of FDI. Policy implications highlight that improving governance quality particularly in regulatory frameworks, transparency, and law enforcement is essential for achieving inclusive and sustainable economic growth.